Improving the identification of high-risk non-metastatic castration-resistant prostate cancer patients in clinical practice - Rosinha, Alina; Rabaça, Carlos; Calais, Fernando; Pinto, João Moreira; Barreira, João Vasco; Fernandes, Ricardo; Ramos, Rodrigo; Fialho, Ana Cristina; Palma dos Reis, José (Frontiers in Oncology, 2024)
Non-metastatic castration-resistant prostate cancer (nmCRPC) represents a challenging disease state in prostate cancer care. nmCRPC patients with a high risk of progression to metastatic disease who are identified by a prostate-specific antigen doubling time (PSADT) ≤10 months are eligible for treatment with the novel androgen receptor inhibitors (ARIs), shown to delay disease progression and extend survival. However, nmCRPC is often unexploited in clinical practice due to a lack of standardization in the methodology and in the tools used for its identification.In this article, a group of Urology and Oncology specialists with acknowledged expertise in prostate cancer reviews the state of the art in the management of high-risk nmCRPC patients, identifies gaps and unmet needs, and proposes strategies to optimize the identification of this patient subgroup in the clinical practice and improve their health outcomes.